Pengaruh Karakteristik Organisasi Terhadap Keberhasilan Implementasi Sistem ERP - V. O. Lawalata (ARIKA, 2012)
International qualification standard owned by ERP system places company in a potential global competitive network to get a highly benefit for their business. However, considering a large amount of fund needed to its investment the failures during acquisition process until its utilization routinely cause fatal impact to the system. This research aims to analize the influence of variables to ERP system implementation success on company. The organizational characteristics based on literature studies tends to effect the level of ERP system implementation success both as a pure influence and strengthened by moderator variables, organizational factors, namely IT asset and IT resource. The results of research on 41 ERP users companies present the relation between characteristics of organization size, centralization, organizational behavior orientation to collaboration, and IT and business short range aligment as factors that have a relevant influence to ERP system implementation success.